Blinatumomab-induced remission followed by haploidentical transplantation in pediatric relapsed/refractory pre-B ALL: a multicenter study in Mexico - Olaya-Vargas, Alberto; Salazar-Rosales, Haydee; Melchor-Vidal, Yadira; Pérez-García, Martín; Herver-Olivares, Annecy; López-Hernández, Gerardo; Ramírez-Uribe, Nideshda; Galván-Díaz, Cesar; Campos-Pérez, Irlanda; Cubria-Juárez, Pilar; Del Campo-Martínez, Angeles; López-Santiago, Norma; et al. (Frontiers in Oncology, 2025)
BackgroundPrecursor B-cell acute lymphoblastic leukemia (pre-B ALL) is the most common pediatric cancer worldwide, with cure rates exceeding 85% in high-income countries. However, in *Mexico*, event-free survival (EFS) during first remission remains below 65%. Children with *relapsed or refractory CD19+ pre-B ALL* have dismal prognoses and limited therapeutic options. This study evaluated the efficacy and safety of *blinatumomab* as a bridge to allogeneic hematopoietic stem cell transplantation (HSCT), including *haploidentical HSCT*, in this high-risk population.MethodsThis multicenter, prospective interventional study was conducted between February 2017 and December 2022 across four pediatric oncology centers in Mexico. Fifty-four patients (aged 8 months to 18 years) with refractory or high-risk relapsed CD19+ pre-B ALL received one or two cycles of *blinatumomab*. Responders were consolidated with allogeneic HSCT. Primary endpoints included remission rates and clinical factors associated with response; secondary endpoints were blinatumomab-related toxicity, overall survival (OS), EFS, and transplant outcomes.ResultsAmong 54 patients, 24 (44.5%) received one cycle, achieving a molecular complete remission rate of 75%. Thirty (55.5%) received two cycles, with 73.3% reaching deep remission (p = 0.89). Forty-one patients (76%) proceeded to HSCT, including 70% who received *haploidentical transplants*. Thirteen did not undergo HSCT due to refractory disease (n = 8) or partial response (n = 5). At 60 months, transplanted patients achieved an OS of 82% and EFS of 68%, with the best survival in matched related donor recipients (100%) versus haploidentical (58%). *Blinatumomab* demonstrated a favorable safety profile with no treatment-related mortality.ConclusionBlinatumomab followed by haploidentical HSCT offers an effective and feasible therapeutic strategy for *relapsed or refractory CD19+ pre-B ALL* in *Mexico*, improving long-term survival in resource-limited settings.